AI-Related Terminology in English as a Reflection of AI Application in Business – A Corpus-Driven Study - Gajšt, Nataša (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
A recent expansion of artificial intelligence (AI) has greatly shaped and impacted our lives, including organizations which use it in their business operations. It has also led to the emergence of AI-related terminology in English. Words such as AI-driven, AI-powered, AI-enabled, and AI-assisted used in business context indicate the complex and rapidly evolving role of AI in business. This study focuses on how these and similar phrases reflect the use of AI in business operations across a variety of industries and functional areas in business organisations. Adopting a corpus-driven approach, we analysed the frequency of selected AI-related phrases across different business sectors as presented in online media reports in English. Our findings show that AI has made its way into a vast range of business operations across different industries. Also, we highlight how these phrases, which may sometimes appear similar, reflect the functional diversity of AI applications. By analysing the scope of and the terminological distinctions between these phrases, our study adds to the clarification of the functions of AI in business and provides a precise vocabulary for discussing its many applications.